Effect of Dominant Follicle Size and GnRH Administration at Fixed-Time Artificial Insemination on Pregnancy Rates in Female Buffaloes on Marajó Island, Brazil - Lima, W.F.; Filho, S.T. Rolim; Ribeiro, H.F.L.; Kumar, S.; Chaves, M.S.; Silva, A.F.B.; Borghese, A.; Vale, W.G. (Journal of Buffalo Science, 2025)
This study aimed to verify the effect of GnRH at the time of artificial insemination and Dominant follicle (DF) diameter on the Pregnancy rate (PR). 384 multiparous upgraded Murrah breed buffalo within 30 to 60 days postpartum with a body condition score of 3.4±0.6 were used. The synchronization protocol consisted of a day 0 (D0) intravaginal device of 1g of P4, application of 2.0mg of BE, and administration of 10 ml of injectable mineral supplementation at 4 pm. On D9, at 4 pm, the device was removed, and injected 0.265 mg of PGF2α and 300 IU of eCG Intramuscular (IM). On day 11, females were categorized based on the size of their dominant follicles. Females with ≥ 13 mm DF were divided into two groups: group 1 received GnRH, while group 2 did not. Similarly, females with < 13 mm DF were split into Group 3, which received GnRH, and Group 4, which did not. At 4 pm, 0.1 mg of GnRH was administered IM according to their groups. On D12, 16 hours after the injection of GnRH (at 8 am), Fixed-time artificial insemination (FTAI) was performed. The pregnancy was diagnosed after 30 days of FTAI by ultrasound. The overall PR was 53.9% (207/384). No significant difference was observed between the groups and follicular size. More pregnancies were observed when the follicle size was around 13mm. It was concluded the administration of GnRH could enhance the efficiency of FTAI in buffaloes.